Understanding the role of university commitment, socioeconomic background, and brand trust in shaping brand loyalty in Islamic higher education in Indonesia - Ahmad Juhaidi; Abdullah M. Al-Ansi; Analisa Fitria; Noor Hidayati; Huriyah (Sustainable Futures)
In the increasingly competitive higher education market, Islamic higher education (IHE) institutions face growing pressure to attract and retain students. Brand loyalty, as a cost-effective competitive advantage, is crucial for IHEs to thrive in this landscape. This study investigates the impact of university commitment, family socioeconomic background, and brand trust on brand loyalty among IHE students. Additionally, the study examines the mediating role of brand trust elements and explores potential gender differences in the relationships between these variables. We collected data from 358 IHE students using questionnaires distributed through convenience and snowball sampling techniques. To analyze the data, we used Partial Least Squares-Structural Equation Modelling (PLS-SEM) multigroup analysis, employing SmartPLS version 4. The findings reveal that university commitment significantly influences both brand loyalty and brand trust. However, family socioeconomic background does not demonstrate a direct effect on brand loyalty. Furthermore, the study finds that brand trust mediates the relationship between university commitment and brand loyalty. Moreover, the study confirms that the impact of trust on loyalty is generally more pronounced in males than in females. To enhance the generalizability of the findings, future research could expand the scope to include a wider array of higher education institutions.